Spatiotemporal variations in life-history traits and statolith trace elements of Sepioteuthis lessoniana populations around northern Taiwan. (10th November 2017) - Ching, Tzu-Yun; Chen, Chih-Shin; Wang, Chia-Hui
Abstract : The bigfin reef squid Sepioteuthis lessoniana is a neritic species widely distributed in coastal waters of the Indo-Pacific region and is of interest to fisheries for its high commercial value. Squid samples were collected from Keelung (KL) and Penghu (PH), around northern Taiwan from October 2012 to September 2013. A total of 949 squid were examined, and 620 squid were aged using statoliths. The age range of the squid in KL (55–183 days) was similar to that in PH (77–186 days). The squid hatched almost year-round, except in January and December in KL. Two seasonal cohorts were identified: a spring cohort (hatched in March to May) and an autumn cohort (July to October). Concentrations of nine trace elements in statoliths were analysed using solution-based inductively coupled plasma mass spectrometry (ICP-MS). Significant differences in Fe/Ca, Cu/Ca and Sr/Ca were found between the two locations, while significant differences in concentration ratios of Sr/Ca and Ba/Ca were noted between the two seasonal cohorts. Results of a principal component analysis and cluster analysis varied in life-history traits between the two geographic stocks and in elemental concentrations between the two seasonal cohorts. Squid in KL and PH might undertake different migration routes, while seasonal variability in oceanographic conditions was apparent in the two locations.